2007
DOI: 10.1007/s00464-006-9129-0
|View full text |Cite
|
Sign up to set email alerts
|

Complications of laparoscopic radical hysterectomy and lymphadenectomy for invasive cervical cancer: experience based on 317 procedures

Abstract: Laparoscopic radical hysterectomy and lymphadenectomy is becoming a routine procedure in the armamentarium of many gynecologists. Complications unique to laparoscopy do exist, but they decrease with repeated training of the procedure and gradually enriched experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…For the knot-tying task, all PGY4's (mean time = 277 s, SD = 1.25) and one PGY1 (time = 235 s) were able to perform the task under the maximum time limit of 6 min (Table 1) as per E-BLUS guidelines [5]. The remaining 12 participants (70.5 %) were not able to complete the intracorporeal suture below the provided 6 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the knot-tying task, all PGY4's (mean time = 277 s, SD = 1.25) and one PGY1 (time = 235 s) were able to perform the task under the maximum time limit of 6 min (Table 1) as per E-BLUS guidelines [5]. The remaining 12 participants (70.5 %) were not able to complete the intracorporeal suture below the provided 6 min.…”
Section: Resultsmentioning
confidence: 99%
“…Major vessel injury (MVI) is an infrequent, but critical complication associated with laparoscopic surgery that leads to blood loss, conversion to open surgery, multiple organ failure, shock, or death [1][2][3]. Intracorporeal knot-tying is a necessary skill for a successful intraoperative repair of a vessel injury and is considered to be a basic skill required to safely practice laparoscopic surgery [4,5].…”
mentioning
confidence: 99%
“…Park et al (2002) reported that in 52 patients with stage IB1 cervical cancer treated with laparoscopic radical hysterectomy and pelvic lymph node dissection, there were 2 cases of ureteral injury (3.8%). Xu et al (2007) reported 5 cases of ureteral injury among 317 cases (1.58%) of laparoscopic radical hysterectomy and pelvic lymph node dissection. Lee et al (2010) reported that of 139 cases of cervical cancer that were treated with laparoscopic radical hysterectomy and pelvic lymph node dissection, only one case (0.72%) showed ureteral injury.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examination provides the most accurate method of ascertaining the degree of metastatic spread to the lymph nodes, although the complications and practical significance of LNE remain controversial. Certain researchers have reported a low therapeutic significance of LNE, however, it causes unavoidable complications that affect the quality of life of the patients (14,15), while others argue that it aids in obtaining a systematic stage for the patient, particularly from the histological aspect (16). Beside the histological type and the invasion depth the of myometrial layer, the lymph node status is extremely significant in the determination of postoperative treatment, particularly radiotherapy (17,18).…”
Section: Discussionmentioning
confidence: 99%